2014
DOI: 10.2166/wh.2014.228
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial pathogens in rural and urban irrigation water

Abstract: The study aimed to compare the bacteriological quality of an urban and rural irrigation water source. Bacterial counts, characterization, identification and diversity of aerobic bacteria were determined. Escherichia coli isolated from both sites was subjected to antibiotic susceptibility testing, virulence gene (Stx1/Stx2 and eae) determination and (GTG) 5 Rep-PCR fingerprinting. Low mean monthly counts for aerobic spore formers, anaerobic spore formers and Staphylococcus aureus were noted although occasional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…The resistance to multiple antimicrobial agents of the E. coli isolates from irrigation water and onions might have been due to the river being downstream of municipal sewage works close to an urban area, as was reported in similar studies in South Africa (1,37). Similar to our study, high resistance to ampicillin was noted in E. coli isolates from the Umgeni and Palmiet rivers (37).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The resistance to multiple antimicrobial agents of the E. coli isolates from irrigation water and onions might have been due to the river being downstream of municipal sewage works close to an urban area, as was reported in similar studies in South Africa (1,37). Similar to our study, high resistance to ampicillin was noted in E. coli isolates from the Umgeni and Palmiet rivers (37).…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this study contribute to the increasing concern about the microbiological quality of surface water sources in South Africa that are used for irrigation and also for drinking water by rural communities (1,9,18,42). However, although the E. coli counts of the primary irrigation source were unacceptably high, a reduction in numbers was observed for the dam water.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Rainfall events increase concentrations of pathogens and indicator organisms in rivers, and reservoirs owing to surface run‐off (Pachepsky et al, ). The use of poor microbiological quality irrigation water further increases the risk of contaminating irrigated produce (Aijuka, Charimba, Hugo, & Buys, ) especially when using overhead irrigation (Castro‐Ibanez et al, ). A previous study indicated the potential effect of contaminated irrigation water on preharvest vegetables (Ijabadeniyi et al, ).…”
Section: Discussionmentioning
confidence: 99%